Analysis of Student's Mathematic Communication Ability in Solving Problems of Pattern Procedures in Pythagoras Theorem - Rizka Abdillah; Yus Mochamad Cholily; Rizal Dian Azmi (Department of Mathematics Education University of Muhammadiyah Malang, 2021)
This study aims at knowing and describing students' mathematical communication skills in problem-solving on Pythagorean theorem material based on Polya's procedure. The Polya's problem-solving phase consists of the stage of understanding problems, planning problem solving, implementing problem-solving plans, and re-examining. The subject of this study were 6 students from eighth-grade of Junior High School which was selected based on good, sufficient, and poor mathematical communication criteria. Moreover, this study employed a descriptive qualitative method where the data was collected by using a test and interview. The results of the study revealed that the students with good mathematical communication capabilities criteria were able to solve the problems based on Polya's procedure. Meanwhile, students with sufficient criteria of mathematical communication capability unable to solve the problem based on Polya's procedure at the stage of making plans by altering mathematical information in the form of picture, students did not realize the need for design actions first, students just go ahead and didn 't see the results of completion that have been made. Additionally, students with poor mathematical communication capabilities were unable to solve the problems based on Polya's procedure, students were not meet at the stage of making plans by changing mathematical information in the form of picture, making plans by using and selecting mathematical information or images to solve the problems, and the students did not look back at the completed results.